The effects of castration followed testosterone supplementation in prostatic complex of Artibeus planirostris (Chiroptera: Phyllostomidae) - Puga, Cíntia C.I. [UNESP]; Beguelini, Mateus R.; Morielle-Versute, Eliana [UNESP]; Vilamaior, Patricia S.L. [UNESP]; Taboga, Sebastião R. [UNESP] (Elsevier, 2016)
The prostatic complex (ventral and dorsal regions) of Artibeus planirostris exhibits seasonal variations throughout the year. Circulating testosterone was correlated with prostate weight, showing an increase from autumn to summer, with the highest peak in summer corresponding to the largest breeding season. This indicates that the level of serum testosterone influences variations in both testicular and prostatic weights. Serum testosterone levels seem to be closely related to the different responses of these glands throughout the year. The castration (consequent suppression of testosterone) and subsequent hormone supplementation may elucidate the relationship of these two glandular types with testosterone. Thus, the aim of this study was to evaluate the effect of castration and the testosterone supplementation in the male prostatic complex of A. planirostris. The results indicated that both prostatic regions were affected by the ablation of testosterone, presenting a decrease in cell proliferation and an increase in apoptosis. Similarly, the prostate was responsive to hormonal supplementation, having a recovery of the active morphophysiological pattern with testosterone supplementation. However, data have shown that the ventral region was more sensitive to changes in testosterone than the dorsal, presenting greater cell renewal.
Keywords: Bat; Castration; Hormone supplementation; Prostate; Testosterone